2015
DOI: 10.3945/ajcn.115.111823
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an early-life intervention on the nutrition behaviors of 2-y-old children: a randomized controlled trial

Abstract: Additional education and support for parents from birth did not improve nutrition behaviors in this population at 2 y of age. This trial was registered at clinicaltrials.gov as NCT00892983.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 39 publications
4
76
1
2
Order By: Relevance
“…We have previously reported that there were no differences in food and nutrient intake at 24 months. 20 There were a few differences in activity-related behaviors: children in the FAB and combination groups spent more time active outside than the control group at 12 months (both, P ≤ .022), and the amount of time spent watching television was lower in the FAB (P = .014) and combination (P < .001) groups compared with the control group at 6 months.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…We have previously reported that there were no differences in food and nutrient intake at 24 months. 20 There were a few differences in activity-related behaviors: children in the FAB and combination groups spent more time active outside than the control group at 12 months (both, P ≤ .022), and the amount of time spent watching television was lower in the FAB (P = .014) and combination (P < .001) groups compared with the control group at 6 months.…”
Section: Resultsmentioning
confidence: 88%
“…18 Dietary intake was assessed by using a validated food frequency questionnaire 26 at 12 and 24 months. 20 Parents indicated how many minutes per week their child spent playing actively outside and inside and watching television at multiple time points. Sleep duration was assessed according to questionnaire responses (parents indicated bed and wake times) and accelerometric findings (24 months only).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…117 Like the Australian trials, the POI trial improved infant feeding practices but had limited impact on child intake and BMI at 2 years of age. 193,194 Eating meals within a family meal setting, reducing screen time, being physically active and achieving adequate sleep (also associated with feeding 131,156 ) are also important determinates of childhood obesity 68 and have been considered in some of the obesity prevention interventions. 195 many early childhood obesity prevention interventions lack these guiding frameworks.…”
mentioning
confidence: 99%